Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm given $f(x)= 3-4\cos(x-2)$

I've gotten to $(-x+3)/4 = \cos(2)\cos(y)+\sin(s)\sin(y)$

But I can't get the $y$ out to create an inverse ...

share|cite|improve this question
you mean $\cos(x-2)$? – Daniel Jul 13 '12 at 4:35
Gah, yes, sorry. – Daniel B. Jul 13 '12 at 4:37
Oh hey wait ... couldn't I take the cosine inverse of both sides, rather than using the difference identity to split it up, I mean. – Daniel B. Jul 13 '12 at 4:41
I think your idea is right – Daniel Jul 13 '12 at 4:49
up vote 4 down vote accepted

Don't expand the $\cos(x-2)$. Solve the whole thing as you normally would, to get $x-2 = \cos^{-1}($something involving $f(x))$, and then just add 2 to both sides.


$$\begin{eqnarray} f(x) & = & 3 - 4 \cos(x-2) \\ \frac14(3-f(x)) & = & \cos(x-2) \\ \cos^{-1}\left(\frac14(3-f(x))\right) &=& x-2 \\ 2+\cos^{-1}\left(\frac14(3-f(x))\right) &=& x\end{eqnarray}$$

share|cite|improve this answer

f(x) = 3 - 4cos(x-2)

we know that f(f^(-1)(x)) = x

write the function f(x) as an equation

y = 3 - 4cos(x-2)

solve the equation for x

x = [arccos((3-y)/4) + 2]

now write the f^(-1)(y)

f^(-1)(y) = [arccos((3-y)/4) + 2]

replace y with x in the equation above

i.e. f^(-1)(x) = [arccos((3-x)/4) + 2]

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.